Habilidades sociais em adolescentes com indicadores de depressão: uma análise através de métodos multimodais - Santos, Gabriela Trombeta (Universidade Federal de São Carlos, 2020)
Current literature studies have been found associations between depression symptoms and social skills déficits. Some authors suggest that research in this area could use multimodal methods as a way to deepen our understanding regarding this phenomenon. In this sense, this research aims (1) to investigate the use of participant-generated photographs as a relevant technology to the production of scientific knowledge, and (2) to identify similarities and differences in social skills repertories of adolescents with and without indicators of depression, considering different sexes and social-economic conditions, through the use of self-report instruments and the Photo-Elicitation method. Results of this work were organized in five articles, three of them related to the first aim of this research and two related to the second one. Study 1 is a systematic review regarding the use of participant-generated photographs in research in the mental health field. Study 2 reflects on my experience in using photo-elicitation with adolescents, justifying its use, presenting particularities of the used methodology and discussing its effects regarding participants' experiences and research results. Study 3 addresses ethical and technical issues involved in the analysis of visual data and describes the data analysis procedure developed for this research. Study 4 is a quantitative study that identifies similarities and differences in the repertoires of social skills of 61 adolescents with and without depression indicators using self-report instruments and Study 5 has the same goal, however, it is a photo-elicitation study, seeking for answers through the analysis of photos and interviews of 8 research' participants. Adolescents between 14 and 17 years old, students from public and private schools, participated in the data collection process of Study 4 and 5. Phase 1 included the application of a General Information Script, The Child Depression Inventory, The Level II Pediatric Anxiety PROMIS and The Brazilian Criteria. In phase 2, The IHSA-Del-Prette Social Skills Inventory was applied and the instructions about taking photographs were given by asking the adolescents to take a set of 12 photographs, in a period of two weeks, regarding the question: "How do I see my life now? ". In Phase 3, semi-structured interviews were conducted with each participant to talk about their pictures. According to Phase 1 and 2 data, reported in Study 4, adolescents with depression indicators reported less elaborate social skills repertories than adolescents without indicators. Boys with depressive symptoms reported the most deficient social skills repertoires. Positive correlations were found between participants' social skills and socioeconomic status and between social skills and the presence of concomitant depression and anxiety symptoms. According to Phase 3 data, reported in Study 5, social skills behaviours were associated with adolescents' perceived support and considered a protective factor for depression mainly during stressful life events. Relationships with parents and new school colleagues were the main sources of social skills challenges. Hobbies were found to facilitate adolescents’ engagement in social interactions.
Social skills in adolescents with indicators of depression: an analysis through multimodal methods
Habilidades sociales en adolescentes con indicadores de depresión: un análisis por medio de métodos multimodales
Keywords: Adolescentes; Adolescência; Depressão; Habilidades sociais; Psicologia; Fotografia; Métodos visuais; Foto-elicitação; Métodos Mistos; Hobbies; Adolescents; Youth; Depression; Social skills; Psychology; Photography; Visual methods; Photo-elicitation; Mixed-methods; Adolescencia; Depresión; Habilidades sociales; Psicología; Fotografía; Métodos visuales; Foto-elicitación; Métodos mixtos; Pasatiempos; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA